Gold-oil-exchange rate volatility, Bombay stock exchange and global financial contagion 2008: Application of NARDL model with dynamic multipliers for evidences beyond symmetry - Muzaffar Asad; Mosab I. Tabash; Umaid A. Sheikh; Mesfer Mubarak Al-Muhanadi; Zahid Ahmad (Cogent Business & Management, 2020)
The primary objective of this research article is to investigate the asymmetrical linkages between gold-oil-exchange rates and Bombay stock indexes by utilizing a nonlinear ARDL approach covering the period from April 2003 to May 2020. Time-series data is divided into three different types of regimes such as before the crisis regime, after the crisis regime, and over the entire period. Seasonality effects within the data series are identified through utilizing different types of unit root analysis such as Philips Peron (PP), augmented dickey-fuller test (ADF), and Kwiatkowski Philips Schmidt Shin (KPSS) test statistics followed by Zivot Andrew (ZA) unit root for identification of structural break unit root test. Nonlinearity within time-series frequencies has been identified through the implementation of BDS test statistics. For longer horizons and before the economic recession period, only gold prices, oil prices, and currency values have an asymmetrical association with Bombay stock indexes as positive shocks to these variables have no impact on stock indexes. However, after the crisis regime and for the longer term, negative shocks to exchange rate fluctuations and oil prices remain statistically insignificant, and only an asymmetrical relationship is established between oil prices and stock indexes. This shows that the regime is more important while classifying the impact of oil prices, gold prices, and appreciation, or depreciation in local currency on Bombay stock indexes. This research article has established an asymmetrical association between stock indexes and gold-oil-exchange rates and concluded asymmetries between them, which are well thought out to be symmetrical by previous researches.
Keywords: 650; Bombay stock exchange; NARDL model with dynamic multipliers; unit root test with structural breaks; oil prices; gold prices; exchange rate fluctuations; macroeconomic volatility